Optimasi Pengelolaan Proyek dengan Sistem Manajemen Data Berbasis Web untuk Meningkatkan Efisiensi dan Akurasi Progres Pekerjaan di Fanaya Art Construction - Badru Salam; Ramayanti, Desi (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
This research aims to design and implement a web-based project management system at Fanaya Art Construction. The system is designed to facilitate project management, from data collection, progress tracking, to automatic report generation. The user interface design approach prioritizes intuitiveness and responsiveness, making navigation easier and ensuring easy access across various devices. The Black Box method is used in system testing to ensure that the system functionality meets user needs. Using CodeIgniter, MySQL, and technologies such as HTML5, CSS3, and JavaScript, the system centrally manages project and client data, accelerates the reporting process, and enhances team collaboration. The implementation of this system has shown improvements in operational efficiency and more transparent and structured project management at Fanaya Art Construction.